Endogenous aging: How statutory retirement age drives human and social capital - Ann Barbara Bauer; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2017)
The return on investments in human and social capital increases in their economic lifetime. Thus, personal, parental, and societal investments in the capacities of individuals take place when these persons are young. Interestingly, the complementary thesis has been widely neglected; investments in the productive capacities of older workers—by the employees themselves, their employers, and their co-workers—should be expected to depend on the time left before retirement. In this paper, we analyze how an increase in the statutory retirement age affects investments in the productivity of older workers. We compare pre- and post-pension reform cohorts and estimate the treatment effect on training participation, job involvement, support from colleagues, and leisure activities. Using a Swiss natural experiment, we find strong support for higher human and social capital investments and the reallocation of time from leisure to work.
Keywords: H55; J14; J24; J26; 330; Pension reform; natural experiment; old-age productivity; human capital; social capital; allocation of time